Effects of 16 weeks of pyramidal and polarized training intensity distributions in well-trained endurance runners - Filipas, L.; Bonato, M.; Gallo, G.; Codella, R. (Scandinavian Journal of Medicine & Science in Sports, 2021)
The aim of this study was to investigate the effects of four different training periodizations, based on two different training intensity distributions during a 16-week training block in well-trained endurance runners. Sixty well-trained male runners were divided into four groups. Each runner completed one of the following 16-week training interventions: a pyramidal periodization (PYR); a polarized periodization (POL); a pyramidal periodization followed by a polarized periodization (PYR?POL); and a polarized periodization followed by a pyramidal periodization (POL_PYR). The PYR and POL groups trained with a pyramidal or polarized distribution for 16 weeks. To allow for the change in periodization for the PYR_POL and POL_PYR groups, the 16-week intervention was split into two 8-week phases, starting with pyramidal or polarized distribution and then switching to the other. The periodization patterns were isolated manipulations of training intensity distribution, while training load was kept constant. Participants were tested pre-, mid- and post-intervention for body mass, velocity at 2 and 4 mmol·L-1 of blood lactate concentration (vBLa2, vBLa4), absolute and relative peak oxygen consumption (VO2peak) and 5-km running time trial performance. There were significant group x time interactions for relative VO2peak (P < 0.0001), vBLa2 (P < 0.0001) and vBLa4 (P < 0.0001) and 5-km running time trial performance (P = 0.0001). Specifically, participants in the PYR_POL group showed the largest improvement in all these variables (~3.0% for relative VO2peak, ~1.7% for vBLa2, ~1.5% for vBLa4, ~1.5% for 5-km running time trial performance). No significant interactions were observed for body mass, absolute VO2peak, peak heart rate, lactate peak and rating of perceived exertion. Each intervention effectively improved endurance surrogates and performance in well-trained endurance runners. However, the change from pyramidal to polarized distribution maximized performance improvements, with relative VO2peak representing the only physiological correlate.